Agent Lion - Soman, David; Davis, Jacky, 1966- (Harper, an imprint of HarperCollinsPublishers, 2020)
"Ms. Flamingo's cat, Fluffy, is missing...and there's only one detective who can crack the case! Meet Agent Lion--he works at Super Detective Agents Agency, wears a tiny blue hat, and loves jelly doughnuts. But most importantly, he is determined to find Fluffy. Agent Lion searches all over Mrs. Flamingo's building--from Mr. Wombat's apartment to the top of the roof--and the missing cat is nowhere to be found. Will Agent Lion ever crack the case?"--Publisher.